2003
DOI: 10.1207/s15328015tlm1501_04
|View full text |Cite
|
Sign up to set email alerts
|

Student Understanding of the Relationship Between the Health Professions and the Pharmaceutical Industry

Abstract: Health professional students' knowledge and attitudes toward the pharmaceutical industry are formed prior to graduation. Professional curricula must address the influences of sales representatives before postgraduate training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 14 publications
1
54
0
Order By: Relevance
“…Studies on medical students' understanding of interactions with PCs can be classified into two groups. The first group includes student exposure to marketing and attitudes towards physician-PC interactions (Hodges 1995;Monaghan et al 2003; Barfett et al 2004;Bellin et al 2004;Vainiomaki et al 2004;Sierles et al 2005;Kumar et al 2006;Hyman et al 2007;Reddy et al 2007). Goodman summarises the common themes of these studies as: (1) student-PC interactions are common (2) students are relatively permissive regarding the acceptance of gifts, and (3) students underestimate the influence of these gifts on their behaviour (Goodman 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on medical students' understanding of interactions with PCs can be classified into two groups. The first group includes student exposure to marketing and attitudes towards physician-PC interactions (Hodges 1995;Monaghan et al 2003; Barfett et al 2004;Bellin et al 2004;Vainiomaki et al 2004;Sierles et al 2005;Kumar et al 2006;Hyman et al 2007;Reddy et al 2007). Goodman summarises the common themes of these studies as: (1) student-PC interactions are common (2) students are relatively permissive regarding the acceptance of gifts, and (3) students underestimate the influence of these gifts on their behaviour (Goodman 2007).…”
Section: Introductionmentioning
confidence: 99%
“…13 The study concluded that students' attitudes about the industry are determined prior to graduation. Student practitioners who will have prescriptive rights (medical and nurse practitioner students) interacted more frequently with pharmaceutical sales representatives than other health professions students and had more positive attitudes about pharmaceutical sales representatives than other students.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, our study shows that the faculty can be a role model on the prescribing habits of the residents. Hence, it is important for medical educators to encourage appropriate rational drug use with critical appraisal competency during the training stages prior to graduation [22]. At the same time, a reliable source that can provide the prescribers with unbiased or two-sided information about the drug is essential.…”
Section: Discussionmentioning
confidence: 99%